The effect of visual merchandising in managing costumer perception (Entrepreneurship Journal for Finance and Business, 2021)
This research aims to achieve Knowing how visual marketing affects costumer impression management is. The following questions were discussed: Are the dimensions of visual marketing available in the field of research? Does this affect the management of the visitors' impression??After the theoretical knowledge of the research variables, the study was conducted on a number of (230) workers as a sample for the study from the community of about (1000) workers in the visitor cities of the Hussaini Holy Shrine in Karbala Governorate. The study tool (the questionnaire) was designed to measure the dimensions of visual marketing as well as the dimensions of managing the visitors ’impression. (230) questionnaires were distributed and (220) were retrieved and only one was not suitable for analysis due to lack of information.The Statistical Package for Social Sciences (SPSS) program was used in measuring the relevant research variables through a study (mean, standard deviation, simple correlation coefficient), and the results of the study indicate a strong direct correlation between visual marketing in its dimensions (facility design, display window, Colors, lighting, and interior presentation) and managing the impression and its dimensions ( focusing on the supervisor, focusing on the self and focusing on work).The study reached a set of conclusions, set of proposals and recommendations were put forward, the most important of which was the need to pay attention to visual marketing tools in order to increase the aesthetics of cities and improve the positive impression on the public of visitors.